Technology: Technological Advances and Changes in Human Lifestyles in a Socio-Cultural Perspective - al Asy ari, M. Khoirul Hadi; Rahman, Muhammad (Proceeding International Conference on Science and Engineering, 2020)
The development of technology in this day and age can not be denied anymore, technology is very fast and rapid development. So it is not surprising that the need for media technology is increasingly high, with the existence of various jobs technology is very easy and quickly done. From that we wrote this paper aims to: (1) know the process of development of technological progress, (2) find out changes in human life patterns due to technological advances, (3) find out the influence of technological advances in the socio-cultural field, and (4) get solutions in overcoming negative impact of technological progress. This paper is the result of a literature study sourced from books, articles, journals, and completed with survey results on the use of modern technology used as data collection techniques. The data obtained were analyzed descriptively critically by the author using the socio-cultural theory change approach. The results of the discussion in this paper show the following: (1) technological advances continue to develop very rapidly and give birth to digital society; (2) there is a change in the pattern of human life due to technological advances so that it becomes more pragmatic, hedonistic, secular, and gives birth to an instant generation but also prioritizes the effectiveness and efficiency in their behavior and actions; (3) technological advances are double faced because they have positive and negative effects on human life; (4) efforts to reduce and overcome the negative impacts of technological progress can be made by synergizing the roles of family, education, society and the state. With data collection methods, documentation and participation in case studies. To obtain maximum and concrete results, this paper can be used as a solution to various problems related to technology.